Strategic Implementation of Academic Supervision by School Principals: A SWOT-Based Analysis of Teacher Professional Development - Af'idah, Azimatul; Hariyati, Nunuk; Haq, Mohammad Syahidul; Khamidi, Amrozi (Journal of Innovation and Research in Primary Education, 2025)
Academic supervision by school principals constitutes a critical mechanism for enhancing teacher professionalism and instructional quality, yet implementation challenges persist globally. This qualitative study employed systematic literature review integrated with field observations at two purposively selected elementary schools in Gresik Regency, Indonesia—UPT SD Negeri 15 and UPT SD Negeri 23—both led by principals with "Guru Penggerak" backgrounds. Data were analyzed using SWOT framework to identify internal and external factors influencing supervision effectiveness. Findings revealed significant improvements in reflection and instructional improvement (8.22-9.09 points) and innovative implementation practices (9.21-9.38 points) at both schools, attributed to structured supervision, active learning communities, and qualified teaching staff. However, teaching methods scores remained suboptimal (59-63 out of 100) with modest increases (1.26-2.00 points), indicating persistent methodological challenges. SWOT analysis identified principal competencies and learning communities as key strengths, time constraints and limited methodological diversity as weaknesses, educational policy support and technological advancement as opportunities, and workload pressures and policy changes as threats. Strategic recommendations include enhancing data-driven supervision mechanisms, strengthening learning communities, providing administrative support systems, and contextually adapting supervision to schools' distinctive excellence programs for optimal teacher professionalism and sustainable instructional quality improvement.